Non-Pharmacological Nursing Management of Edema in Acute Kidney Injury: A Case Study of Ankle Pump Exercises and 30° Leg Elevation - Dewi Diniyatul Maulidiyah; Muhammad Zulfatul A’la; Murtaqib; Sujarwanto (Health and Technology Journal (HTechJ), 2026)
Acute Kidney Injury (AKI) frequently induces sodium retention and hypoalbuminemia, precipitating severe peripheral edema that threatens cardiopulmonary and neurological stability. Non-pharmacological interventions are increasingly sought to safely and effectively manage this complex fluid overload in clinical settings. This case study aimed to evaluate the clinical efficacy of a combined nursing intervention, specifically structured ankle pump exercises and 30-degree leg elevation, in mitigating peripheral edema severity in an adult patient with AKI. A descriptive, single-subject case study design was employed within a regional hospital ward setting. The intervention was administered twice daily over a consecutive five-day period. Edema severity was quantitatively assessed at baseline and post-intervention utilizing a standardized pitting edema observation sheet to measure precise tissue depth and rebound time. The intervention yielded clinically meaningful improvements by the third day of implementation. Bilateral lower extremity edema successfully decreased from Grade III to Grade II, accompanied by a measurable reduction in pitting depth and improved tissue recoil time. These objective findings demonstrate enhanced venous return and successful mobilization of interstitial fluid. Ankle pump exercises combined with 30-degree leg elevation represent a highly viable, cost-effective, and independent nursing strategy for managing peripheral edema in AKI patients. This non-pharmacological approach safely complements standard medical management, empowering patient self-care while circumventing the iatrogenic risks associated with aggressive pharmacological diuresis.